Nanoformulated water-soluble paclitaxel to enhance drug efficacy and reduce hemolysis side effect. (July 2017) - Gu, Weiting; Chen, Jie; Patra, Prabir; Yang, Xiaoyan; Gu, Quanrong; Wei, Lingxuan; Acker, Jason P; Kong, Beihua
Surgery, chemotherapy, and radiotherapy are the three top cancer treatment modalities. Paclitaxel (PTX) is one of the most widely used chemotherapy drugs. However, its clinical applications have been significantly limited due to: (i) serious hemolysis effect of currently available commercial paclitaxel formulations and (ii) its water insolubility. An easy way to deliver paclitaxel by a new nanocarrier system using pluronic copolymers of P123/F68 and Sorbitan monopalmitate (Span 40) was reported in our previous research article. The characterization of the formulation and analysis of drug release and cellular uptake were also presented. In this article, we reported discoveries of our follow-up in vivo antitumor and in vitro hemolytic study discoveries. The experimental results showed that the nanoformulated PTX achieved much better tumor suppression performance while reducing hemolysis side effects. This newly formulated drug can significantly improve patient outcomes in cancer chemotherapy.